Expression of empathy in a Facebook-based diabetes support group. (October 2018) - Pounds, Gabrina; Hunt, Daniel; Koteyko, Nelya
Highlights: Empathic communication is well represented in the investigated Facebook site. Empathic communication is integrated with information and advice. Empathic communication is shaped by Facebook's dialogic affordances and constraints. Overall, group members prefer to provide rather than seek support from each other. Abstract: Existing studies show that people suffering from chronic illnesses turn to online health communities not only to share and check relevant factual information but also to receive and express empathy from/to their fellow sufferers. Indeed, along with seeking and providing advice from and to others, expressions of social support, including empathic features, have been found to be central to discourse in online support groups (OSGs). This is the first study to use a pragmatics-based discourse analytic approach that focuses on "empathic communicative acts" (Pounds and De Pablos-Ortega, 2016) to investigate the expression of empathy on a social networking site (SNS), and specifically in a Facebook support group or FSG. The analysis is applied to 560 messages to a type 2 diabetes FSG and explores how empathy is expressed within the multi-dialogic context of asynchronous interaction. The study helps qualify the supportive value of FSGs and provides the basis for further studies of empathic communication in other SNS contexts.